THE DROSOPHILA HOMOLOG OF VERTEBRATE MYOGENIC-DETERMINATION GENES ENCODES A TRANSIENTLY EXPRESSED NUCLEAR-PROTEIN MARKING PRIMARY MYOGENIC CELLS - Paterson, BM; Walldorf, U; Eldridge, J; Dübendorfer, A; Frasch, Manfred; Gehring, WJ (Proceedings of the National Academy of Sciences of the United States of America, 1991)
We have isolated a cDNA clone, called Dmyd for Drosophila myogenic-determination gene, that encodes a protein with structural and functional characteristics similar to the members of the vertebrate MyoD family. Dmyd clone encodes a polypeptide of 332 amino acids with 82% identity to MyoD in the 41 amino acids of the putative helix-loop-helix region and 100% identity in the 13 amino acids of the basic domain proposed to contain the essential recognition code for muscle-specific gene activation. Low-stringency hybridizations indicate that Dmyd is not a member of a multigene family similar to MyoD in vertebrates. Dmyd is a nuclear protein in Drosophila, consistent with its role as a nuclear-gene regulatory factor, and is proposed to be a transiently expressed marker for muscle founder cells. We have used an 8-kilobase promoter fragment from the gene, which contains the first 55 amino acids of the Dmyd protein, joined to lacZ, to follow myogenic precursor cells into muscle fibers with antibodies to beta-galactosidase and to Dmyd. Unlike the myogenic factors in vertebrate muscle cells, Dmyd appears to be expressed at a much lower level in differentiated Drosophila muscles, so Dmyd cannot be followed continuously as a muscle marker. This fact is reflected in the loss of Dmyd RNA expression in 12- to 24-hr embryos, a major period of early myogenesis, as well as in the undetectable level of the nuclear antigen in primary cultures of embryonic and adult Drosophila muscle.
Keywords: INSECT MYOGENESIS; HELIX-LOOP-HELIX; INVERTEBRATE MYOD